Plant Phenolics and Phenolic-Enriched Extracts as Antimicrobial Agents against Food-Contaminating Microorganisms - Miklós Takó; Erika Beáta Kerekes; Carolina Zambrano; Alexandra Kotogán; Tamás Papp; Judit Krisch; Csaba Vágvölgyi (MDPI AG, 2020)
Phenolic compounds and extracts with bioactive properties can be obtained from many kinds of plant materials. These natural substances have gained attention in the food research as possible growth inhibitors of foodborne pathogenic and spoilage bacteria. Many phenolic-enriched plant extracts and individual phenolics have promising anti-quorum sensing potential as well and can suppress the biofilm formation and toxin production of food-related pathogens. Various studies have shown that plant phenolics can substitute or support the activity of synthetic food preservatives and disinfectants, which, by the way, can provoke serious concerns in consumers. In this review, we will provide a brief insight into the bioactive properties, i.e., the antimicrobial, anti-quorum sensing, anti-biofilm and anti-enterotoxin activities, of plant phenolic extracts and compounds, with special attention to pathogen microorganisms that have food relation. Carbohydrase aided applications to improve the antimicrobial properties of phenolic extracts are also discussed.